1996
DOI: 10.1007/bf02445158
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of experimental drug addiction with antibodies to serotonin and dopamine

Abstract: K A. Evseev, L. A. Basharova, et aL 819 0.29 mg/dl in the control (n=5, p<0.01). It is known that synthesis of the acute phase proteins in the liver is induced by the products of activated phagocytes [9].These results suggest that the previously described NK-induced changes in the blood system are associated not only with the stress-realizing systems but also with activation of phagocytizing cells. Eur. J. Cancer., 26, No. 5, 641-644 (1990). 9. H. Baumann and J. Gauldie, lmmunol. Today, 15, No. 2, 74-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Since the development of neuropathological syndromes is accompanied by enhanced production of autoantibodies against neurotransmitters [3,4,6], anti-5-HT antibodies can be regarded as a new class of natural peripheral analgesics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the development of neuropathological syndromes is accompanied by enhanced production of autoantibodies against neurotransmitters [3,4,6], anti-5-HT antibodies can be regarded as a new class of natural peripheral analgesics.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that induction of specific antibodies against neurotransmitters, in particular, against serotonin, reduces alcohol intake in experimental alcoholism [4], prevents the development of abstinent symptoms in experimental morphinism and alcoholism [1,5,6], and reduces abstinent morphine-induced hyperalgesia in nociceptive thermal injury [3]. In light of this, it seems interesting to use artificial induction of anti-5-HT antibodies for producing an analgesic effect in inflammatory pain syndromes.…”
mentioning
confidence: 99%
“…However, the method of suppression of positive reinforcing effect of morphine in the animals with anti-SMAP antibodies, utilized in this study, has an advantage concluding in that that it realizes blockade of intra-cellular transduction of serotonin signal supporting formation of complex of bright positive emotions after delivering into the organism the addictive drugs having different chemical structure. In some articles successful application of immunochemical approach, particularly antibodies to serotonin and catecholamines for correction of drug addiction to morphine in the rats, is presented [16].…”
Section: Researchmentioning
confidence: 99%
“…Alcohol-or morphine-withdrawal syndrome serves as a psychophysiological correlate of stress syndromes [2]. Our previous studies showed that immunization with a conjugate of 5-HT and bovine serum albumin (BSA) alleviates symptoms of withdrawal in experimental animals [3,4]. Production of antibodies (AB) against 5-HT and BSA produces opposite effect on alcohol withdrawal.…”
mentioning
confidence: 99%